Nonprofit Advocacy at the American Heart Association: Creating a Visionary Way Forward at Our 40th Anniversary. Issue 19 (11th May 2021) - Churchwell, Keith; Antman, Elliott; Birnbaum, Jill; Desai, Nihar R.; Harrington, Robert A.; Holubowich, Emily J.; Ivy, Kendra N.; Schoeberl, Mark; Warner, John J.; White, Courtney J.; Whitsel, Laurie P.; Yancy, Clyde
Abstract : In 2021, the American Heart Association celebrates its 40th anniversary in advocacy. This policy statement details the arc of the organization's nonpartisan, evidence-based, equity-focused approach to advocating for public policy change, highlighting key milestones and describing the core components of the association's capacity and activity at all levels of government. This policy statement presents a vision and strategic imperative for future American Heart Association advocacy efforts to inform and influence policy changes that advance equitable, impactful societal solutions that transform and improve cardiovascular health for everyone. The American Heart Association maintains accountability by measuring and evaluating the totality of this work and its impact on equitable health outcomes. The American Heart Association will apply these lessons to constantly refine its own strategic policy focus and advocacy efforts. The association will also serve as a resource and catalyst to other organizations working to engage and educate policy makers, partners, the media, and funders about the important role and contribution of public policy change to achieve shared goals.